Renal Denervation in Patients With Uncontrolled Hypertension and Confirmed Adherence to Antihypertensive Medications. Issue 6 (5th October 2015) - Hameed, Mohammed Awais; Pucci, Mark; Martin, Una; Watkin, Richard; Doshi, Sagar; Freedman, Jonathan; Riley, Peter; Townend, Jonathan; Crowe, Paul; Lipkin, Graham; Dasgupta, Indranil
Abstract : Renal denervation (RDN) has emerged as a potential device‐based treatment for resistant hypertension. The authors present their experience of the use of catheter‐based RDN as part of routine clinical care in two specialist hypertension clinics. Thirty‐four patients with uncontrolled hypertension underwent RDN. All patients had ambulatory blood pressure (BP) monitoring and directly observed medication administration prior to the procedure to exclude white‐coat hypertension and nonadherence, respectively. Overall, there was a significant change in clinic systolic BP of −15.1 mm Hg (95% confidence interval, −23.4 to −6.8; P =.001) and clinic diastolic BP of −6.2 mm Hg (95% confidence interval, −11.5 to −0.9; P =.02) 6 months postprocedure, and a nonsignificant change in daytime ambulatory BP of −5.4/−2.9 mm Hg. Eighteen patients (51.4%) showed a significant reduction in their clinic systolic BP (≥10 mm Hg) and 16 (47%) had a significant reduction in their daytime ambulatory systolic BP (≥5 mm Hg) at 6 months.